EVALUASI KELAYAKAN USAHA PENGOLAHAN DAGING BUAH PALA (Studi Kasus Usaha Pengolahan Daging Buah Pala di Desa Karegesan Kecamatan Kauditan Kabupaten Minahasa Utara) - Rini M. Supit; Jen Tatuh; Rine Kaunang; Vicky R.B. Moniaga (Universitas Sam Ratulangi, 2015)
ABSTRACT Rini Maria Supit. Evaluation of Nutmeg Fruit Meat Processing Business (Case Study Nutmeg Fruit Meat Processing Business in the village Karegesan Kauditan District of North Minahasa Regency) (under the guidance of Prof. Dr. Ir. Jen Tatuh, MS as a Chairman, Dr. Rine Kaunang, SP., MBA and Ir. Vicky R.B Moniaga, MSi as Members). The aimed of this study to evaluate feasibility of various aspect from Nutmeg Business in Karegesan village. Data collected for seven months, from June 2014 through December 2014. The data obtained are primary and secondary data. Primary data were obtained from interviews with the owner of Nutmeg Fruit Meat Processing Business in Karegesan village, and secondary data obtained through the literature related to the nutmeg processing business. The method is carried out to analyze the feasibility investment by measuring the Net Present Value, Internal Rate of Return and Net Benefit / Cost. Based on the results of research and discussion, it can be concluded from the various aspects of this business is feasible to run. It can be seen from the Net Present Value which reached a positive value (IDR 1.427.565.679,00), Internal Rate of Return of 1,84%, and Net Benefit / Cost at 17,2. Keywords: Feasible Study, Nutmeg